Album poetry and early poetry by Lesya Ukrainka - Borzenko, Olexander (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The article considers the influence of the album tradition on the early work of Lesya Ukrainka: the disclosure of the features of this influence is the main purpose of this investigation. Landscape poetry is characterized by cordiality, simplicity and sincerity, usually consistent with some real or hypothetical everyday situation. Album work has its own characteristics, among which the most common are the simplicity of images, private themes, sentimentality and didactics. Ukrainian album lyrics maintained a close connection with folk art, in particular with the song. Hence the widespread use of permanent images of folklore origin and stylistic clichés, their repetition in different variations. During her literary growth, Lesya Ukrainka actively used the artistic experience of album lyrics. She was most interested in the thematic complex of youth: growing up, personal formation and self-awareness, expanding ideas about people and the world. The poetess revealed the topic of love popular in women’s albums in general stereotypically - as a drama of sincere but undivided feelings. Her lyrical heroine cultivates faith in life and hope in spite of unfavorable fate. In the poetic expression of the author in the early period of her work was very attracted to the vivid imagery, pathos and a certain melodramatics, in part this led to the presence in her poetry of emphasized picturesqueness, evocative intonations, demonstrative emotions. At the same time, in some of Lesya Ukrainka’s early works there is a noticeable readiness to partially rethink the expressive possibilities of the album tradition by searching for complications and combining them with other sources. In the process of interaction with the album experience, gradually, more and more fully, from work to work, the independent creative profile of the young author was expressed.